Pyrolysis characteristics and kinetic analysis of coconut shell and nutmeg shell for potential source of bioenergy - K. Ashwini; R. Resmi; Retheesh Reghu (Engineering Science and Technology, an International Journal, 2024)
This study explores the pyrolytic characteristics of coconut shells and nutmeg shells as potential bioenergy sources, addressing a research gap in comparing their energy potential. It employs analytical techniques like Field Emission Scanning Electron Microscopy, Fourier Transform Infrared Analysis, and Thermogravimetric Analysis for surface morphology analysis, volatile compound detection, and pyrolysis process investigation. Using kinetic analysis methods, such as ASTM E2070 - Method A, Friedman, and Vyazovkin, thermodynamic properties like enthalpy, Gibbs free energy, and entropy are determined at a single heating rate. Activation energy, pre-exponential factors, and thermodynamic values are presented for both materials. Coconut shells exhibit higher activation energies, indicating greater thermal stability, especially in ASTM E2070 - A and Friedman methods. In contrast, nutmeg shells have lower activation energies, suggesting simpler decomposition. Thermodynamic evaluations favor coconut shells, highlighting increased disorder during pyrolysis compared to nutmeg shells. These findings offer insights into their thermal degradation kinetics, informing potential applications in pyrolysis processes.